If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -54 = 5x + -55 Reorder the terms: -54 + 6x = 5x + -55 Reorder the terms: -54 + 6x = -55 + 5x Solving -54 + 6x = -55 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -54 + 6x + -5x = -55 + 5x + -5x Combine like terms: 6x + -5x = 1x -54 + 1x = -55 + 5x + -5x Combine like terms: 5x + -5x = 0 -54 + 1x = -55 + 0 -54 + 1x = -55 Add '54' to each side of the equation. -54 + 54 + 1x = -55 + 54 Combine like terms: -54 + 54 = 0 0 + 1x = -55 + 54 1x = -55 + 54 Combine like terms: -55 + 54 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 14=23+5 | | 5-x=11-2x | | 4x+20+5x-5=87 | | f(X)=9830(x)+50(x) | | 5y^2-10x=2 | | 7(6-2a)=5(-3a+1)x | | -5(1-3p)=35+7p | | 3x+-2y=3 | | 2x+3x=5.70 | | 2x-5=8x+10-x | | 0=4x^2+32x+48 | | f+3/8=21/4 | | 4a+.4=1.6 | | f(x)=4x^2+32x+48 | | 6x^2+xy-2y^2+7x+7y-3=0 | | y=-5x+90 | | 0=.25x^2+x-15 | | 6x-2y+24=0 | | 5x^2+25x+4=2 | | 8x-7=3x+38 | | 8N+3=3n-4n | | 4+2x[36-(18+5)]= | | 4(x+2)-.5x=29 | | Xspuared-6x=27 | | 83/4+r=11/8 | | x-3=sqrt(4x)+9 | | 5[8-y]=30 | | 17=2p-3 | | x^3+y^3-xy+y^2=0 | | 4x+71=-33+8x | | 21+3t=9-3t | | 7b+2=13-b |